Biological and demographic parameters of Tegolophus brunneus (Acari: Eriophyidae) in citrus - de Morais, Matheus Rovere [UNESP]; Zanardi, Odimar Zanuzo; de Andrade, Daniel Júnior [UNESP] (Springer Nature, 2019)
The brown citrus rust mite, Tegolophus brunneus Flechtmann (Acari: Eriophyidae), causes citrus rust, as does Phyllocoptruta oleivora (Ashmead) (Acari: Eriophyidae). As the citrus rust damage has intensified in recent years and T. brunneus has been reported in high population levels in several regions of Brazil, this mite has caused concern to growers and technicians. Because T. brunneus has been little studied and its bioecological characteristics are unknown, this study investigated the biological and demographic parameters of T. brunneus on citrus fruits under laboratory conditions. Our results showed that the egg incubation period and viability were 3.0 and 94.5%, respectively. The larval and nymphal stage durations were 1.1 and 2.8 days, respectively. The development time of the immature stage was 6.9 days, with 92.3% survival. When females and males were maintained together, the sex ratio of offspring was 0.7; virgin females produced only males. The pre-oviposition (from adult emergence to the first egg) and total pre-oviposition (egg-to-egg) periods were 1.6 and 8.5 days, respectively. Fecundity was 8.5 eggs, and female and male longevities were 13.2 and 11.4 days, respectively. The estimate of demographic parameters indicated that the Ro and T of T. brunneus were 6.45 offspring and 13.0 days, and r and λ were 0.142 and 1.153 day−1, respectively. These results suggest that T. brunneus has high growth potential on citrus trees. Therefore, management strategies may be required to reduce the population levels and damage caused by T. brunneus in citrus groves.
Keywords: Citrus brown mite; Citrus sinensis; Demographic parameters; Integrated pest management